Novel methods for synthesizing halide-free alane without the formation of adducts - Dinh, L.; Knight, D.; Paskevicius, Mark; Buckley, Craig; Zidan, R. (Springer, 2012)
Many of the current synthesis methods for aluminium hydride (alane—AlH3) involve reacting AlCl3 and LiAlH4 in solvents. The reaction requires the formation of an alane adduct such as AlH3•[(C2H5)2O] prior to obtaining crystallized stable a-AlH3. This process requires several hours of pumping in a vacuum system to remove the ether and convert the alane etherate into stable a-alane. This crystallization process is both costly and hazardous because a large amount of highly flammable material (e.g. ether) is removed by vacuum pumps over several hours. Conversely, the work presented herein describes novel methods to synthesize adduct-free alane. It is demonstrated here that AlH3 can form by mixing AlCl3 and LiAlH4 in the solid state and heating to 75°C; only a-AlH3 was obtained. The a-AlH3 product can be washed with minimal solvents leading to zero formation of alane adducts. In addition, the unwanted LiCl by-product is also removed during the solvent wash, resulting in halide-free a-alane. Although simply mixing and heating the reactants led to a 40% yield of alane, having the reactants compacted and mechanically pressed while heating increases the yield to 60% crystalline a-AlH3.